Antioxidant Activities and Total Phenolic Content of Macroalgae from Central Coast of Vietnam - Thi Thanh Van, Tran; Mai Nhu Hieu, Vo; Nguyen Ha Vi, Tran; Minh Ly, Bui; Thi Thu Thuy, Thanh (Asian Journal of Chemistry, 2013)
Antioxidant activities and total phenolic content of ethanolic extract of 41 marine algae species including red, brown and green algae from central coast of Vietnam were evaluated. The extract of Sargassum polycystum, Chnoospora implexa, Chnoospora minima demonstrated great DPPH radical scavenging activity with EC50 values (0.08, 0.2; 0.26 mg dry extract/L; respectively), extract from Dictyota dichotoma was found to be highest total antioxidant capacity (19.6 mg ascorbic acid equivalent/g dry seaweed) and Sargassum microcystum exhibited highest ferric reducing activity (23.1 mg Fe2+ equivalent/g dry seaweed). We found that only green algae showed a linear correlation between total phenolic content and antioxidant activities.